Assessing the Influence of Motivation and Compensation on Employee Performance at the Bandar Lampung Health Service - Saadillah, Dinu; Yuliana, Yuliana; Nadhirah, Aulia (Jurnal Bisnis Mahasiswa, 2025)
The motivation and compensation used by companies are one way for employees to achieve company goals through good performance. Bandar Lampung City Health Service employees are one of the government agencies engaged in the health sector. This research aims to assess whether motivation and compensation impact the performance of Bandar Lampung City Health Service employees. The research method used in this research is a quantitative approach. The method used is the multiple linear regression analysis method, and the purposive sampling method was used to determine the sample. The population used was Bandar Lampung City Health Service employees, totalling 70 respondents. Observation findings show that motivation and compensation influence the performance of Bandar Lampung City Health Service employees.